Social support mediates the relationship between depression and subjective well-being in elderly patients with chronic diseases: Evidence from a survey in Rural Western China - Zhonglian Li; Suxia Qin; Yafen Zhu; Quanxiang Zhou; Aijing Yi; Caiyun Mo; Jun Gao; Juhai Chen; Tianhui Wang; Zhanhui Feng; Xiangang Mo (PLoS ONE, 2025)
Background The aging population has led to a marked increase in the prevalence of chronic diseases among the elderly, significantly impacting their physical and mental health, as well as their overall quality of life. In rural regions of Western China, these challenges are exacerbated by limited access to medical insurance, low living standards, and inadequate mental health services. Consequently, the physical and mental well-being of elderly individuals with chronic conditions in these areas warrants focused attention. This study aims to investigate the interrelationships between depression, social support, and subjective well-being, with particular emphasis on the mediating role of social support. Methods This cross-sectional study involved a survey of 2,156 elderly individuals aged 60 and above, all living with chronic diseases in the rural areas of Qiannan, Guizhou, China. Pearson correlation and hierarchical linear regression analyses were employed to explore the relationships between the variables. A structural equation model was then constructed using Amos 23.0, based on the identified correlations between depression, social support, and subjective well-being. The bootstrap estimation method was applied to assess the mediating effect of social support in the depression-subjective well-being relationship. Results The analysis revealed a significant negative correlation between depression and subjective well-being, while social support showed a strong positive association with subjective well-being. Mediation analysis confirmed that social support significantly mediates the relationship between depression and subjective well-being, accounting for 10.23% of the total effect. Notably, the influence of subjective support on depression and subjective well-being was found to be more pronounced than that of objective support or social support utilization. Conclusions The findings highlight the necessity of strengthening the social support system for elderly individuals with chronic diseases in rural Western China, particularly by enhancing psychological and emotional support. This approach is crucial for mitigating depressive symptoms and improving subjective well-being in this population.